Long-term exposure of human proximal tubule cells to hydroxycobalamin[c-lactam] as a possible model to study renal disease in methylmalonic acidurias - Sauer, Sven; Opp, Silvana; Schumann, Anke; Okun, Jürgen G.; Kölker, Stefan; Morath, Marina (Journal of inherited metabolic disease, 2009)
Dysfunction of proximal tubules resulting in tubulointerstitial nephritis and chronic renal failure is a frequent long-term complication of methylmalonic acidurias. However, the underlying pathomechanisms have not yet been extensively studied owing to the lack of suitable in vitro and in vivo models. Application of hydroxycobalamin[c-lactam] has been shown to inhibit the metabolism of hydroxycobalamin and, thereby, to induce methylmalonic aciduria in rats, oligodendrocytes, and rat hepatocytes. Our study characterizes the biochemical and bioenergetic effects of long-term exposure of human proximal tubule cells to hydroxycobalamin[c-lactam], aiming to establish a novel in vitro model for the renal pathogenesis of methylmalonic acidurias. Incubation of human proximal tubule cells with hydroxycobalamin[c-lactam] and propionic acid resulted in a strong, time-dependent intra- and extracellular accumulation of methylmalonic acid. Bioenergetic studies of respiratory chain enzyme complexes revealed an increase of complex II-IV activity after 2 weeks and an increase of complex I and IV activity as well as a decrease of complex II and III activity after 3 weeks of incubation. In addition, human proximal tubule cells displayed reduced glutathione content after the exposure to hydroxycobalamin[c-lactam] and propionic acid.
Gesehen am 08.08.2023